2017
DOI: 10.1002/trtr.1590
|View full text |Cite
|
Sign up to set email alerts
|

Text Structure Strategies for Improving Expository Reading Comprehension

Abstract: Comprehending expository reading material is a challenge for many students. Research has shown that students’ expository reading comprehension can improve with the help of text structure instruction. The purpose of this article is to present teachers with a framework for effectively implementing text structure instruction in their classrooms. Within this framework, the authors suggest four possible learning objectives for text structure instruction. They then describe instructional strategies related to each o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 15 publications
1
38
0
1
Order By: Relevance
“…In text structure instruction, authentic texts can be contrasted with controlled exemplar texts, which are carefully crafted to exemplify particular text structures and their elements (e.g., Williams et al, 2016). Teachers use single-structure exemplar texts in the initial phases of text structure instruction (Jones, Clark, & Reutzel, 2016) and teach students strategies for analyzing particular structures, such as using a note frame to organize important information (e.g., Roehling, Hebert, Nelson, & Bohaty, 2017). Explicit instruction and practice with controlled exemplar texts may serve as a form of scaffolding to strengthen students’ mental representations of text structures (Meyer & Ray, 2011).…”
Section: Text Structure Instructionmentioning
confidence: 99%
See 1 more Smart Citation
“…In text structure instruction, authentic texts can be contrasted with controlled exemplar texts, which are carefully crafted to exemplify particular text structures and their elements (e.g., Williams et al, 2016). Teachers use single-structure exemplar texts in the initial phases of text structure instruction (Jones, Clark, & Reutzel, 2016) and teach students strategies for analyzing particular structures, such as using a note frame to organize important information (e.g., Roehling, Hebert, Nelson, & Bohaty, 2017). Explicit instruction and practice with controlled exemplar texts may serve as a form of scaffolding to strengthen students’ mental representations of text structures (Meyer & Ray, 2011).…”
Section: Text Structure Instructionmentioning
confidence: 99%
“…Before learning to identify and analyze the author’s use of multiple structural elements in an authentic text, students must be able to identify single text structures (Jones et al, 2016). This initial phase of text structure instruction is often implemented with controlled exemplar texts (e.g., Roehling et al, 2017). After mastering single structures, students are ready to apply their cumulative knowledge to a more authentic and complex text.…”
Section: Text Structure Instruction With Authentic Textsmentioning
confidence: 99%
“…Text structure instruction has been identified as an effective strategy for improving the expository reading and writing skills of students, especially those with learning disabilities (Duke & Pearson, 2002;Gersten, Fuchs, Williams, & Baker, 2001;Roehling, Hebert, Nelson, & Bohaty, 2017). Hebert, Bohaty, Nelson, and Brown (2016) found that these strategies were particularly effective when writing was involved and also found larger effect sizes for students with learning disabilities.…”
Section: Teach Children Text Structuresmentioning
confidence: 99%
“…Students listened and understood the material delivered by teachers. Introvert personality type tended to learn on their own rather than collaborating, thus, providing learning with individual work methods making introvert students comfortable and easy to understand (Howorth et al, 2016;Mills et al, 2019;Roehling et al, 2017;Sugiharta, 2019;Syarofah, Wiryokusumo, & Sugito, 2019). In expository learning, the teacher explained the objectives and material to be discussed in learning.…”
Section: Discussionmentioning
confidence: 99%